Association between ABO, Rh blood groups, lip and dermatoglyphic patterns, and nonsyndromic oral clefts: A case-control study - Nimisha Sivanand; Mohammed Junaid; B Sivapathasundaram; Manikandhan Ramanathan; Hermann F Sailer; J E Nijesh; Shyam Sivasamy; Preetha Elizabeth Chaly (Wolters Kluwer Medknow Publications, 2021)
Objective: The objective of the study is to determine the association between nonsyndromic oral clefts (OC) in children and ABO, Rh blood groups, lip, and dermatoglyphic patterns of their unaffected parents. Methods: This case-control study was conducted at a tertiary cleft center in Chennai, India, among 240 individuals comprising 80 units (40 cases and controls, respectively). Each unit (triad) was constituted by a child (0-12 years of age) either born with nonsyndromic OC (cases) or with no diagnosed congenital anomaly (control) and their unaffected parents (mother and father). ABO and Rh blood groups, specific lip print, fingerprint pattern, and palmar asymmetry were recorded for each individual. Strength of association of related factors was assessed by multivariable logistic regression reported as adjusted odds ratios and 95% confidence interval. Results: A1-positive blood group was found to be considerably higher among case mothers (14.39 [1.57-32.27]). A higher odds of OCs were observed among case mothers with whorl lip pattern (1.51 [1.16-3.17]) and radial loop pattern in fingers (1.44 [1.09-2.31]) relative to controls. In addition, palmar asymmetry was distinctively higher among case parents compared to controls (P < 0.01). Conclusion: Findings indicate that A1-positive blood group, higher frequency of whorl lip, and radial loop finger patterns in mothers and higher ulnar loop pattern in fathers and palmar asymmetry in both parents increases odds of occurrence of OC among their offspring. These identifiable traits offer potential scope for better service planning among resource-constrained disadvantaged communities in India.